The spatial analysis of Yamama Formation heterogeneity in south of Iraq - Handhal, Amna M. (Iraqi Journal of Science, 2022)
This study focuses on determining the heterogeneity of Yamama Formation and its spatial distribution in south of Iraq using three indices namely, Coefficient of Variation, Lorenz Coefficient, and Dykstra – Parsons Coefficient. The porosity and permeability values from eleven wells in south of Iraq (Basra and Maysan oil fields) are used for computing heterogeneity indices. Ordinary kriging technique is used to interpolate the computed indices and to show the spatial distribution of these indices over the study area. Results indicated that the average values of Lorenz and Dykstra – Parsons Indices are 0.73 and 0.86, respectively which refer to the extremely heterogeneity nature of Yamama Formation in the study area.The spatial distribution of the heterogeneity indicates that the heterogeneity of Yamama Formation increases from southeast to northeast and follows the same trend of decreasing formation thickness. Results from this study could be helpful in managing production plans in the southern Iraqi fields and enhance oil recovery project.